Enkätundersökning om skogsägare inom Norrskogs upptagningsområde - Granlöf, Daniel (SLU/School for Forest Management, 2012)
The purpose of this report is to find out what different preferences forest owners have in the region where Norrskog have their operation area, what they prefer and think about Norrskog. The purpose is also to compare some of the questions to a similar study that was made in 2008. The study is made in cooperation with Norrskog which is a forest owner cooperative. Norrskog has about 13 000 members which is about half of all forest owners in the region. To get the answers from the forest owners, questionnaires were sent out by mail. 371 were sent out and 102 came back. There were more members of Norrskog that responded than it was nonmembers. The results indicate that the forest owners have long term perspectives, their priorities are to nurse the forest so they can get the profit later on. The majority of the forest owners are relatively old, more than 50 % are over 60 years old and that can be the reason way the majority prefers to have their information from Norrskog by mail and not by e-mail. In the nearest five years the most common activity among the forest owners are clearing, 74 % are in need of that activity.